Impact of Intraprocedural Pressure Changes on Hemodynamic Outcome During Self-Expanding TAVR - Pykäri Jouni; Vasankari Tuija; Ylitalo Antti; Porela Pekka; Paana Tuomas; Malmberg Markus; Laurila Sanna; Koskinen Juho; Koivisto Tero; Savontaus Mikko (SPRINGER LONDON LTD, 2026)
Introduction: During the transcatheter aortic valve replacement (TAVR) procedure, hemodynamic measurements can be used to evaluate transcatheter heart valve (THV) performance. We hypothesized that the occurrence of a significant decrease in invasive aortic pressure immediately after annular contact by a self-expanding THV indicates effective annular sealing. This phenomenon could thus be used as a marker for the occurrence of paravalvular leak (PVL).
Methods: Thirty-eight patients undergoing TAVR procedure with a self-expandable Evolut R or Evolut Pro (Medtronic) valve prosthesis were included in the study. Drop in aortic pressure during valve expansion was defined as a decrease in systolic pressure of 30 mmHg immediately after annular contact. The primary endpoint was the occurrence of more than mild PVL immediately after valve implantation.
Results: A pressure drop was seen in 60.5% (23/38) of patients. More than mild PVL requiring balloon post-dilatation (BPD) was significantly more frequent in patients who did not have a systolic pressure decrease > 30 mmHg during valve implantation (46.7% [7/15] vs. 13.0% [3/23], respectively; p = 0.03). Patients without a systolic pressure decrease > 30 mmHg also had a lower mean cover index on computed tomography analysis (16.2% vs. 13.3%; p = 0.016). The 30-day outcomes were similar between the two groups, and echocardiography at 30 days demonstrated more than none/trace PVL in 21.1% (8/38) of patients, with no difference between the two groups.
Conclusion: A decrease in aortic pressure after annular contact is associated with an increased probability of good hemodynamic outcome after self-expanding TAVR implantation. In addition to other methods, this parameter could be used as an additional marker for optimal valve positioning and hemodynamic outcome during the implantation procedure.